Vaccination Decisions and Social Capital in Japan - Toshihiro Okubo; Ilan Noy (CESifo GmbH, 2024)
The COVID-19 vaccines played a pivotal role in safeguarding populations. Yet, vaccine hesitancy remained a significant barrier to increasing coverage rates, as many high-income countries faced prolonged vaccine refusal campaigns. In Japan, vaccine doses were administered under a reservation system accessible via a website and by phone. Achieving a high vaccination coverage for a vaccine that was offered at no financial cost was still surprisingly difficult in Japan. In many countries, vaccine hesitancy during the pandemic has been closely related to people's trust in their governments given governments' controversial social distancing mandates. In Japan, lockdowns were voluntary, and vaccinations were also not mandated. As there were no significant political conflicts about the government's policies, vaccination acceptance was influenced by more basic tenets, and here we focus here on social capital, defined as cohesive resources that enable a society to function effectively. Social capital, in this context, refers to community trust, collaboration, and engagement that create social bonds between individuals and society. Using a unique, large, survey, administered repeatedly through the years of the pandemic, we mostly found support, for the hypothesis that social capital matters for the vaccination decision; and that it matters even once we control for institutional trust (especially trust in the medical system). However, this general association between trust in other community members, trust in the willingness of community members to engage in reciprocal assistance, and trust in the more general willingness of the community to support individuals, were all associated differently with the vaccination decision, and with the views about vaccinations. From a policy perspective, this suggests that the Japan case both exposes the relevance of trust in government, in other circumstances, but also shows that intra-community trust (i.e., social capital), is important even in contexts when governmental trust is not a significant issue.
Keywords: I12; 330; vaccine; Covid-19; social capital; trust